The current situation regarding the availability and accessibility of anticancer drugs for breast cancer in the Peruvian public health systems - Valencia-Mesías, G (2021)
The availability of effective, accessible, safe and high-quality anticancer drugs for the medical treatment of cancer is fundamental in ensuring optimal healthcare in the public health system in Peru. The main objective is to assess the current situation regarding anticancer drugs (termed 'high-cost') for breast cancer, as well as an analysis of the possible factors which negatively impact access to the Peruvian public health systems.There are similarities in the availability of anticancer drugs, since most treatments are covered by the Peruvian Ministry of Health. EsSalud offers an extra monoclonal antibody (pertuzumab) in the metastatic treatment stage. Meanwhile, the National Institute of Neoplastic Diseases (INEN), mainly for metastatic disease, has relied on more tested treatments over the last year. An agreement has been reached with the armed forces, which will enable patients to receive oncology care at the INEN and, thereby, benefit from the use of high-cost drugs.